The CaChiVI2 Gene of Capsicum annuum L. Confers Resistance Against Heat Stress and Infection of Phytophthora capsici - Ali, Muhammad; Muhammad, Izhar; ul Haq, Saeed; Alam, Mukhtar; Khattak, Abdul Mateen; Akhtar, Kashif; Ullah, Hidayat; Khan, Abid; Lu, Gang; Gong, Zhen-Hui (Frontiers in Plant Science, 2020)
Extreme environmental conditions seriously affect crop growth and development, resulting in substantial reduction in yield and quality. However, chitin-binding proteins (CBP) family member CaChiVI2 plays a crucial role in eliminating the impact of adverse environmental conditions, such as cold and salt stress. Here, for the first time it was discovered that CaChiVI2 (Capana08g001237) gene of pepper (Capsicum annuum L.) had a role in resistance to heat stress and physiological processes. The full-length open-reading frame (ORF) of CaChiVI2 (606-bp, encoding 201-amino acids), was cloned into TRV2:CaChiVI2 vector for silencing. The CaChiVI2 gene carries heat shock elements (HSE, AAAAAATTTC) in the upstream region, and thereby shows sensitivity to heat stress at the transcriptional level. The silencing effect of CaChiVI2 in pepper resulted in increased susceptibility to heat and Phytophthora capsici infection. This was evident from the severe symptoms on leaves, the increase in superoxide (O2—) and hydrogen peroxide (H2O2) accumulation, higher malondialdehyde (MDA), relative electrolyte leakage (REL) and lower proline contents compared with control plants. Furthermore, the transcript level of other resistance responsive genes was also altered. In addition, the CaChiIV2-overexpression in Arabidopsis thaliana showed mild heat and drought stress symptoms and increased transcript level of a defense-related gene (AtHSA32), indicating its role in the co-regulation network of the plant. The CaChiVI2-overexpressed plants also showed a decrease in MDA contents and an increase in antioxidant enzyme activity and proline accumulation. In conclusion, the results suggest that CaChiVI2 gene plays a decisive role in heat and drought stress tolerance, as well as, provides resistance against P. capsici by reducing the accumulation of reactive oxygen species (ROS) and modulating the expression of defense-related genes. The outcomes obtained here suggest that further studies should be conducted on plants adaptation mechanisms in variable environments.